Approaches are considered to planning of theatrical placards for différent their operating conditions (Pedagogy of Higher and Secondary Education, 2007)
The method of the associative planning is expounded on the example of playbill fo r raising of tragedies V. Shakespeare.
Keywords: placard; conception, associations; attribute; composition